EKOLOGI KALDE FEMINISME MELAYU DETERMENISME, EKOTURISME MELAYU DAMPAK GLOBALISASI - Putri Rahma Dani; Yasnel (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to examine the relationship between Kalde ecology, Malay feminism, cultural determinism, ecotourism, and the impact of globalization on Malay society. This study is qualitative with a descriptive-analytical design that aims to explore in depth the views and experiences of Malay society in managing ecosystems, the role of women, and the impact of global culture. This study also explores the potential of Malay ecotourism as a tool to strengthen ecological sustainability and community economic empowerment, amidst the flow of globalization that brings significant changes to local cultural and economic values. The research methods used include in-depth interviews, participant observation, and surveys to obtain data from Malay society involved in ecotourism activities. The results of the study are expected to provide insight into how ecology and feminism are interconnected in maintaining cultural and environmental sustainability, and how the impact of globalization affects Malay cultural identity.